Catalan constitutional influence in the statute of the sicilian region - Concetta Basile, Maria (Cuadernos de Historia del Derecho, 2018)
The work exposes the way followed by Italy in 1947 for the approval of the special legislation for Sicily in order to solve certain problems of territorial organization. Based on the ideas of Gaspare Ambrosini, the possible influence on the form and content of Catalonia’s Statute of Autonomy, approved at the time of the Spanish Second Republic is shown, as well as the similarities and differences between the two texts, fruit of very different constitutional realities, however connected in some specific points.
Keywords: Sicily; Catalonia; Regional Statute; Autonomy; Gaspare Ambrosini.